PTU-008 Rigid sigmoidoscopy: a dying skill in gastroenterology?. (17th June 2017) - Selvaraj, E; Gorard, D
Abstract : Introduction: Rigid sigmoidoscopy is a cost-effective tool to rapidly investigate lower gastrointestinal symptoms in outpatient clinics. Since rigid sigmoidoscopy rarely inspects mucosa proximal to the rectum, it is diagnostically inferior to flexible sigmoidoscopy. However it allows early diagnosis/treatment of ulcerative colitis, and in excluding colitis in young patients with diarrhoeal symptoms, it obviates the need for (expensive) flexible endoscopy. With increased accessibility to flexible sigmoidoscopy, we hypothesised that rigid sigmoidoscopy use has declined. Unlike the general surgery curriculum, there is no formal requirement in the gastroenterology curriculum or structured training to achieve competence in this procedure. Method: This study aimed to assess the level of experience and training in rigid sigmoidoscopy received by current UK gastroenterology trainees. An online survey was disseminated via the British Society of Gastroenterology Trainee Chair to 850 gastroenterology trainees throughout the UK. The survey was open for a 4 week period. Results: 164 trainees responded (19.3% response rate). Respondents were fairly evenly distributed from different stages of training: LAS 1%, ST3 14%, ST4 20%, ST5 19%, ST6 15%, ST7 14% and Out-of-Programme 17%. 57% respondents had never performed a rigid sigmoidoscopy, 23%<5 procedures and only 10% had performed >20 procedures. Of those trainees performing rigid sigmoidoscopy, 12% had been supervised in performing >5 procedures, 70% in performing 1–4 procedures, and 18% stated they had never received supervision. Of trainees performing rigid sigmoidoscopy, 90% use it only in clinic, while 10% were able to perform sigmoidoscopy on inpatients; only 4.5% obtain written consent. 99% of trainees had not undertaken a formal DOPS assessment, 76% felt that training in rigid sigmoidoscopy was non-existent, 15% insufficient and 8% just adequate. 55% felt that rigid sigmoidoscopy would be a useful tool in clinic and 51% would like it to be incorporated into the curriculum. For future trainees, 24% felt that no formal training is required but 57% felt that formative and summative DOPS should be undertaken. The average waiting time for flexible sigmoidoscopy was 2–4 weeks in 51% of responses and >4 weeks in 30% of responses. 76% trainees said that their current supervising consultant did not perform rigid sigmoidoscopies. Conclusion: Rigid sigmoidoscopy is not a widely used or taught procedural skill among current gastroenterology trainees. Trainees agree that there needs to be a more structured approach to teaching and training in rigid sigmoidoscopy with formal assessments of competency. Unless the expectation is that future UK consultant gastroenterologists will not use rigid sigmoidoscopy, the British Society of Gastroenterology needs to lead in ensuring the technique is taught to trainees. Disclosure of Interest: None Declared